IMPLEMENTASI PROGRAM LITERASI DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Jefrianto (JURNAL ILMU BUDAYA, 2021)
This study aims to explain the condition of the literacy program in Indonesian language learning at SMA Negeri 1 Konawe Selatan, Southeast Sulawesi Province. This research used descriptive qualitative research. The results showed that the literacy program was not running optimally. The problems of literacy programs in Indonesian language learning that occur at SMA Negeri 1 Konawe Selatan include irrelevant learning strategies, the availability of facilities and infrastructure that are less supportive and incomplete, and low reading interest in students as shown in the questionnaire results as much as 57% students do not agree to set aside their time for reading activities, 48% of students do not agree that reading activities are preferable to playing, 57% of students answered agree that reading activities are only done when they get assignments. This shows that the literacy program has not been running effectively to increase interest in reading and writing in students.